2013
DOI: 10.1149/2.092401jes
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Electrochemical Decomposition of Fluoroethylene Carbonate on Silicon Anode Surfaces in Lithium Ion Batteries

Abstract: Fluoroethylene carbonate (FEC) shows promise as an electrolyte additive for improving passivating solid-electrolyte interphase (SEI) films on silicon anodes used in lithium ion batteries (LIB).We apply density functional theory (DFT), ab initio molecular dynamics (AIMD), and quantum chemistry techniques to examine excess-electron-induced FEC molecular decomposition mechanisms that lead to FEC-modified SEI. We consider one-and two-electron reactions using cluster models and explicit interfaces between liquid el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
216
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(238 citation statements)
references
References 68 publications
21
216
1
Order By: Relevance
“…We speculate that the fast release of F À and SO 2 may be correlated to the high cycling performance exhibited by the Si-PYR 13 FSI system. This argument dovetails with earlier modelling studies of FEC decomposition, which show that FEC also rapidly releases F À to form LiF, as well as empirical data, showing favourable Si half-cell cycling behaviour when using FEC as an electrolyte additive in organic carbonate-based electrolyte 45 .…”
Section: Articlesupporting
confidence: 83%
See 2 more Smart Citations
“…We speculate that the fast release of F À and SO 2 may be correlated to the high cycling performance exhibited by the Si-PYR 13 FSI system. This argument dovetails with earlier modelling studies of FEC decomposition, which show that FEC also rapidly releases F À to form LiF, as well as empirical data, showing favourable Si half-cell cycling behaviour when using FEC as an electrolyte additive in organic carbonate-based electrolyte 45 .…”
Section: Articlesupporting
confidence: 83%
“…2e,g, respectively). The same model surface was previously studied in the context of fluoroethylene carbonate (FEC) decomposition 45 and represents a low-potential anode surface with Si directly exposed to the liquid electrolyte, serving as an electron source that can readily reduce electrolyte molecules in its vicinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of higher concentrations of F for cells cycled with electrolytes containing FEC is likely due to the reduction of FEC generating additional LiF in the SEI on the surface of the Sn electrode. [22][23][24][25][26] The SEI for cells cycled with electrolyte containing FEC has a similar evolution to the SEI for the cells cycled with the standard electrolyte, although the evolution results in significantly less capacity fade and related electrolyte decomposition (Table I). 27 Hard XPS (HAXPES).-The C 1s core level HAXPES spectra of the cycled tin anode taken with photon energies of 1487 eV (lab XPS), 2200 eV, and 5000 eV are provided in Figure 5.…”
Section: 19-23mentioning
confidence: 78%
“…It will be shown that FEC nearly suppresses the reduction of any other electrolyte component, which is consistent with the previous literature and suggests that the rate of FEC reduction is greater than the reduction of EC and linear carbonates. [26][27][28][29][30][31] Furthermore, due to the continuous consumption of FEC quantified by 19 F-NMR, the number of charge/discharge cycles over which silicon anodes can by stabilized by FEC is directly proportional to the total moles of FEC per …”
mentioning
confidence: 99%